A Comparative Study of Performance of the Medical Students of Nepal in Anatomy on the Basis of PBL and Traditional Teaching - Yadav, Birendra Kumar (International Journal of Pharmaceutical & Biological Archive, 2013)
A Comparative Study of Performance of the Medical Students of Nepal in Anatomy on the Basis of PBL and Traditional Teaching